The reaction mechanism investigation of sulfonamides with OH radical by DFT - Aydogdu, Seyda; Hatipoglu, Arzu (ELSEVIER, 2022)
Sulfonamides (SAs) are an important group of antibiotics. Due to their widespread use, they have been found as micropollutants in different ecosystems. The presence of SAs in the environment is a serious threat to human health. Degradation reactions of SAs with OH radicals are important for their removal from the environment. This study aims to predict the reaction mechanisms of selected six SAs with center dot OH radical by the DFT method. For this purpose conceptual DFT has been applied to SA + OH degradation reactions to find possible reaction paths. The electronic properties, global and local descriptors of SAs have been calculated. Global and local descriptors are good parameters to predict the reaction mechanisms. Local descriptors were used to find the most suitable sites for the attack of the hydroxyl radical and to predict all possible products. The proposed products and mechanism of the reactions are in agreement with experimental data.
Keywords: DFT; Sulphonamides; OH radical; Global descriptors; Local descriptors; PHOTOCATALYTIC DEGRADATION; SULFA DRUGS; PHOTODEGRADATION; HYDROXYL; KINETICS; TIO2; SULFAMETHOXAZOLE; SULFAPYRIDINE; ANTIBIOTICS; OXIDATION; Chemistry